Integrated 18F-T807 Tau PET, Structural MRI, and Plasma Tau in Tauopathy Neurodegenerative Disorders - Li, Cheng-Hsuan; Chen, Ta-Fu; Chiu, Ming-Jang; Yen, Ruoh-Fang; Shih, Ming-Chieh; Lin, Chin-Hsien (Frontiers in Aging Neuroscience, 2021)
Background: Tau-specific positron emission topography (PET) imaging enables in vivo assessment of Alzheimer’s disease (AD). We aimed to investigate its performance in combination with plasma tau levels in patients with non-AD tauopathy. Methods: A total of 47 participants were enrolled, including 10 healthy controls, 16 with tauopathy parkinsonism syndromes (9 with corticobasal syndrome [CBS], 7 with progressive supranuclear palsy [PSP]), 9 with frontotemporal dementia (FTD), 4 with AD, and 8 with Parkinson’s disease (PD). All participants underwent clinical assessments, 18F-T807 tau PET, brain MRI, and plasma tau assay. Results: The global cortical standard uptake value ratio (SUVR) of 18F-T807 PET was comparable between PD and control (p = 0.088). The cortical SUVR was significantly higher in AD group (p = 0.002) and modestly increased in PSP group compared to the PD group (p = 0.044), especially in parietal and pallidal regions. Asymmetric 18F-T807 uptake at the pallidum was noted in patients with CBS and FTD. Cortical tau tracer uptake was associated with increased plasma tau level (p = 0.016), especially in frontal and parietal regions. Regional tracer uptake was correlated with cortical thinning in patients with CBS and PSP (CBS: r = -0.092, p = 0.025; PSP: r = -0.114, p = 0.015). Conclusions: The 18F-T807 tau tracer uptake was robustly increased in AD group but only modestly increased in patients with PSP. Although the cortical tau tracer uptake correlated with regional cortical atrophy and plasma tau levels, a four-repeated tau-specific tracer is needed for future classifying tauopathy parkinsonism syndromes.